Analisis Efisiensi Pengelolaan Dana Zakat Infak Sedekah (ZIS) di Baznas Kabupaten/Kota Se-Karesidenan Surakarta dengan Menggunakan Metode Data Envelopment Analysis Dea - Azhar Alam (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
Efficiency is one measurement of the organization operational succes including the charity management organization. This study measures and analyzes the efficiency of BAZNAS in Surakarta residency using the DEA (Data Envelopment Analysis) method. Efficiency results show which BAZNAS regency / city is efficient or inefficient and find out the source of inefficiency. Having optimal operational (CRS), there were found 4 BAZNAS with 100% efficiency, namely BAZNAS Klaten Regency, Surakarta City, Sragen Regency, and Wonogiri Regency. While some BAZNAS with efficiency below 100% are BAZNAS Boyolali Regency (87.6%), Sukoharjo Regency (73.5%) and Karanganyar Regency (59.9%). Efficiency analysis with VRS assumption shows that all BAZNAS in Surakarta Residency have 100% optimal efficiency. The source of inefficiency that occurs in some BAZNAS Districts that have efficiency scores below 100% is that the potential of zakat distribution, distribution of infaq, and the total distribution of infaq & zakat has not been optimized.